Will the requirement by the US FDA to simultaneously co-develop companion diagnostics (CDx) delay the approval of receptor tyrosine kinase inhibitors for RTK-rearranged (ROS1-, RET-, AXL-, PDGFR-α-, NTRK1-) non-small cell lung cancer globally? - Ou, S.-H.I (2020)
10.3389/fonc.2014.00058